STUDI GEOLOGI DAN LITOFASIES UNTUK MENENTUKAN KUALITAS BATUGAMPING SEBAGAI BAHAN BAKU SEMEN PADA PT CEMINDO GEMILANG (DESA LEBAK TIPAR, KECAMATAN CILOGRANG, KABUPATEN LEBAK, PROVINSI BANTEN): GEOLOGY AND LITHOFACIES STUDIES TO DETERMINE THE QUALITY OF LIMESTONE AS A RAW MATERIAL FOR CEMENT AT PT CEMINDO GEMILANG (LEBAK TIPAR VILLAGE, CILOGRANG DISTRICT, LEBAK REGENCY, BANTEN PROVINCE) - Ardi Darmawan, Muh. Nanda; Rinal Khaidar Ali; Wahyu Budhi Khorniawan (Buletin Sumber Daya Geologi, 2024)
Cement factory PT. Cemindo Gemilang which is located in Lebak city, has done many exploration activities which in this area also has the potential for limestone resources. Basically, the research area has a quite large potential for limestone and never been mined before. Therefore this research can help to determine the geological condition in the research area including geomorphology, lithology, and geological structure as well as determining prospect zones regarding the distribution of good quality according on modeling's results which can later be done for mining activities. The research location is in Lebak Tipar Village, Cilograng District, Lebak City, Banten Province. The methods used are geological mapping, petrographic analysis, and geochemical analysis and the modeling is done based on the Inverse Distance Weghting (IDW)Method. The results of the research show that the research area is composed of four lithologies from the youngest to the oldest are sandstone, limestone, mudstone(Citarate Formation) and mudstone(Cijengkol Formation) with a developed structure whic is shown with the indications of broken fractures. Based on the petrographic analysis that has been done, the research area is divided into four lithofacies, namely wackestone, packstone, and grainstone which show good quality with high CaO levels of around >50%, while the mudstone lithofacies has poor quality because it has low CaO levels of around <50%. Based on analysis of surface and subsurface samples, it shows that in the research area the good quality limestone is predominantly in the central to western part of the plot while the poor quality limestone is found in the eastern part of the plot.